India in Africa: Trade goods and connections of the late first millennium - Jason D. Hawkes; Stephanie Wynne-Jones (Afriques)
Archaeological approaches to the study of Indian Ocean connections tend to focus on “foreign” objects that appear in different contexts. In East Africa, these objects are found at settlements on what would become the Swahili coast, and they show that these settlements were linked to Indian Ocean networks from as early as the 7th century AD. The limited quantities of these remains mean that these earliest connections are difficult to see; they become much easier to identify from the 11th century onwards, when the largest numbers of goods are known. Yet our ability to trace these earliest connections is not only affected by the amount of evidence at our disposal. The ways that archaeologists have approached this topic have been dominated by historical paradigms that focus on the Persian Gulf and the agency of Arab merchants and consider Indian Ocean connections primarily in terms of trade. This article reviews the ways that this commercial emphasis creates a particular way of thinking in archaeological scholarship and discusses the fact that within this framework connections between India and Africa are poorly accounted for. It then turns to think about traces of these connections in the archaeology of the 7th to 10th centuries in both of these regions. Drawing on the strengths of archaeology in thinking through the meaning and use of material objects, it explores the ways in which a variety of artefact categories evoke a number of different types of connections between the people of India and Africa across the Indian Ocean.